Analisis Deformation, Stress, dan Safety Factor pada Geometric Properties Crane Hook - Johan Wayan Dika; Abi Suwito; Sunardi Sunardi; Titik Sugiarti (University of Merdeka Malang, 2022)
Crane hook strength analysis is an effort to minimize accidents and work failures when used in moving goods that tend to have heavy loads. Apart from that, the analysis is also used as a benchmark for the crane hook safety level which can be identified through the accompanying structures. This study aims to determine the strength of the crane hook with various geometric shapes and sizes, namely the ST E 355 crane hook with the DIN 15401 standard, hereinafter referred to as the original size and half of the original size. The strength in question consists of deformation, stress and safety factor. This research begins with the design process using an autodesk inventor, then proceeds to the simulation and analysis process through ANSYS. The results obtained are the crane hook with the original size has the best strength. This is indicated by a small deformation with a value of 0.82214 mm, a low stress value of 264.14 Mpa, and a high safety factor with a value of 2.668903.